Information Systems for Crisis Response and Management in Mediterranean Countries 4th International Conference, ISCRAM-med 2017, Xanthi, Greece, October 18-20, 2017, Proceedings - Dokas, Ioannis M.; Bellamine-Ben Saoud, Narjès; Dugdale, Julie; Díaz, Paloma (Lecture Notes in Business Information Processing, 2017)
XVI, 221 p. 54 illus.